Relation of interleukin-6 level with coronary artery disease severity in patients undergoing coronary angiography - (:unkn) unknown (AVES, 2020)
Objective: Atherosclerosis plays an important role in the pathogenesis of coronary artery disease (CAD). There is a closer relationship between atherosclerosis and inflammatory cytokines. Commonly used scoring systems for risk stratification in clinical practice are GENSINI and SYNergy between PCI with TAXUS and Cardiac Surgery (SYNTAX) scores for determining disease severity and method of revascularization. The aim of this study was to investigate the relationship between interleukin (IL)-6 levels and both GENSINI and SYNTAX scores in patients with CAD. Methods: In total, 118 patients who underwent coronary angiography were enrolled in the study. GENSINI and SYNTAX were calculated for determining disease severity. IL-6 level was measured using immunometric assay method. Results: There were no significant differences between the groups with respect to mean age, blood pressure, heart rate, and use of alcohol. Gender and smoking status were significantly different between the groups. GENSINI and SYNTAX scores of patients were significantly higher in the CAD group than in the controls. IL-6 level was significantly higher in the CAD group than in the controls. In the correlation analysis, IL-6 level significantly correlated with GENSINI and SYNTAX scores and was an independent predictor of abnormal coronary angiography. Optimal cut-off level of IL-6 was 7.81 pg/mL to assess the ability of IL-6 to differentiate the presence of CAD (area under curve, 0.78; sensitivity, 78.3%; and specificity, 70.7%). Conclusion: Patients with CAD have higher IL-6 levels compared with the controls. IL-6 level correlated with both GENSINI and SYNTAX scores. Moreover, IL-6 was an independent predictor of abnormal coronary angiography. An IL-6 value of >= 7.81 pg/mL predicted the presence of CAD with a sensitivity of 78.3% and a specificity of 70.7%.
Keywords: Coronary artery disease; Inflammation; IL-6; GENSINI score; SYNTAX score; NECROSIS-FACTOR-ALPHA; INFLAMMATION; TOCILIZUMAB; MORTALITY; RISK